Heavy Metal(oid)s in Soil–Tea System: Sources, Bioaccumulation, and Risks in Eastern Dabie Mountain - Minxuan Luo; Tian Liu; Jinyan Huang; Honggen Xu; Ting Jiang; Xiang Xie; Yujing Yang (Land)
Yuexi County, a key tea-producing area in eastern Dabie Mountain, may face potential heavy metal(oid) (HM) contamination risks due to nearby mining and intensive agricultural activities. This study investigated seven HMs (As, Cd, Cr, Hg, Ni, Pb, and Zn) in paired soil–tea samples using multiple analytical approaches, including the geoaccumulation index (Igeo), the potential ecological risk index (RI), bioconcentration factor (BCF), and positive matrix factorization (PMF) with Monte Carlo simulation for health risk assessment. Results showed that Zn (82.65 mg/kg) and Cd (0.15 mg/kg) were the most enriched HMs in soils with higher Igeo values than other HMs. PMF analysis identified four major HM sources: mining and transportation (27.75%), agricultural activities (26.90%), natural soil parent material (26.17%), and industrial emissions (19.18%). Tea plants exhibited selective HM absorption, with Hg showing the highest bioaccumulation (BCF = 0.45), while As, Cr, and Pb had minimal uptake (BCF < 0.05). Although health risk assessments confirmed that both non-carcinogenic and carcinogenic risks from soil and tea consumption were within safe limits for adults and children, Cr and Ni required special attention due to their risk contributions. Overall, ecological and health risks in the region were found to be low. These findings provide important scientific support for pollution monitoring, risk management, and overcoming trade barriers in tea-growing regions with acidic soils. Future research should integrate HM speciation analysis with seasonal monitoring to further optimize tea plantation management strategies.